Improving Work Performance And Employee Performance Through Employee Leadership And Commitment In Bali Province - Sucipta, Nyoman; Ardani, Wayan; Mulyani, Putu Ari (Transforma Jurnal Manajemen, 2024)
The company has a goal to develop and progress according to the predetermined target, so that it can compete with other companies. To achieve the company's goals, of course employees are required to maximize the work performance and performance achieved by employees. Work performance and employee performance can be influenced by various factors, including in this study the emphasis is on leader behavior and employee work commitment. The purpose of this study is to determine the increase in work performance and employee performance through leader behavior and employee work commitment in Bali Province in general, using a review method from the results of previous studies with the main variables on these variables. The methodology used by the author in compiling this article uses an exploratory qualitative approach by reviewing the results of previous studies with related variables, by utilizing the Google search engine on the Google Scholar site. This study uses a review of the results of ten previous studies in a maximum period of 5 years ago, it was concluded that leader behavior and employee commitment have a positive and significant influence on employee work performance and performance variables. Based on this conclusion, it is expected that the Company can prioritize conducive and relatively directing leader behavior and employee commitment can be considered with an increase in achieving the expected work performance and employee performance. Thus, employees will have high initiative to complete the work given by the company.